Profitability, financial leverage, size, dan underpricing stock price - Wendy Salim Saputra; Alfredo Brendis Yuliman; Bella Cynthia Lesmana W (LPMP Imperium, 2023)
his study aims to prove the relationship between profitability, financial leverage, and firm size on stock price underpricing in manufacturing companies listed on the IDX during the 2017-2019 period. This study uses a hypothesis test method to analyze the relationship between profitability, financial leverage, and firm size on stock price underpricing. This study uses 73 manufacturing companies listed on the IDX that carried out IPOs during the 2017 – 2019 period. This test was carried out using SPSS statistical software version 25. The results of this study are that profitability and company size variables influence underpricing stock prices, while leverage has no effect against underpricing of stock prices. Public interest statement The results of this research can practically be used as material for company considerations in managing a company before conducting an IPO, and it is hoped that this research can add to the accounting research literature in the field of financial accounting and management accounting.